2021
DOI: 10.15252/embj.2020107238
|View full text |Cite
|
Sign up to set email alerts
|

Golgi maturation‐dependent glycoenzyme recycling controls glycosphingolipid biosynthesis and cell growth via GOLPH3

Abstract: Glycosphingolipids are important components of the plasma membrane where they modulate the activities of membrane proteins including signalling receptors. Glycosphingolipid synthesis relies on competing reactions catalysed by Golgi‐resident enzymes during the passage of substrates through the Golgi cisternae. The glycosphingolipid metabolic output is determined by the position and levels of the enzymes within the Golgi stack, but the mechanisms that coordinate the intra‐Golgi localisation of the enzymes are po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
74
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 59 publications
(82 citation statements)
references
References 89 publications
6
74
0
Order By: Relevance
“…Logo plot analyses showed that those which bind to GOLPH3/3L have a clear enrichment of basic residues next to the TMD, with blank values dominating further from the TMD, indicating that many of the cytoplasmic tails are not longer than 6-10 residues. Leucine residues are the second most abundant in some positions, consistent with reports that a L-x-x-R/K or L-L-R/K-R/K motifs contribute to binding to GOLPH3 or its yeast ortholog Vps74 (Ali et al, 2012; Tu et al, 2008; Rizzo et al, 2021). We also applied the same analysis to type II proteins that were classified as degraded or non-degraded in the ΔGOLPH3;ΔGOLPH3L cell line, and amongst the degraded set there was a very similar enrichment of membrane-proximal positive residues, again followed by blanks indicative of short cytoplasmic tails.…”
Section: Resultssupporting
confidence: 88%
See 4 more Smart Citations
“…Logo plot analyses showed that those which bind to GOLPH3/3L have a clear enrichment of basic residues next to the TMD, with blank values dominating further from the TMD, indicating that many of the cytoplasmic tails are not longer than 6-10 residues. Leucine residues are the second most abundant in some positions, consistent with reports that a L-x-x-R/K or L-L-R/K-R/K motifs contribute to binding to GOLPH3 or its yeast ortholog Vps74 (Ali et al, 2012; Tu et al, 2008; Rizzo et al, 2021). We also applied the same analysis to type II proteins that were classified as degraded or non-degraded in the ΔGOLPH3;ΔGOLPH3L cell line, and amongst the degraded set there was a very similar enrichment of membrane-proximal positive residues, again followed by blanks indicative of short cytoplasmic tails.…”
Section: Resultssupporting
confidence: 88%
“…1 B). Amongst the interacting Golgi enzymes identified by mass spectrometry, several of the previously reported cargo interactors were identified as hits including GCNT1, EXT1, EXT2, GALNT12, POMGNT1, ST3GAL4 and B4GALT5 (Rizzo et al, 2021; Pereira et al, 2014; Eckert et al, 2014; Isaji et al, 2014; Chang et al, 2013; Ali et al, 2012). Comparing the 73 Golgi-resident membrane proteins enriched by either GOLPH3 or GOLPH3L (P <0.05 compared to GST alone), there was a high degree of overlap (42 common hits, 13 GOLPH3-specific and 18 GOLPH3-specific).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations